The Effectiveness of the Aceh Ombudsman Representative’s Maladministration Handling: An Insider Perspective - Muazzinah, Muazzinah; Akmal, Saiful; Fadhil, Amrul; Fathurrahman, Reza (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2022)
The Ombudsman of the Republic of Indonesia oversees public services, particularly timely responses to reports. Since 2018, the Aceh Representative of the Indonesian Ombudsman handled 150 reports. It is interesting to investigate how well the Ombudsman dealt with these reports. This study examines the effectiveness of the Aceh Representative of the Indonesian Ombudsman in handling reported maladministration cases using a qualitative approach. The research data were gathered through interviews and document reviews by referring to Steer’s (1976) formulation of organization effectiveness, which includes productivity, adaptability, communication, job satisfaction, and human resources. The productivity, communication, and flexibility indicators are adequately effective, although not directly involved in handling cases. The handling is limited to coordinative meetings with local authorities assigned to resolve the problems. However, the findings also reveal that job satisfaction indicators are ineffective, as evidenced by the absence of community satisfaction survey findings to assess their performance. Likewise, the results on the resource indicator were ineffective since the human resources were not allocated according to the Aceh Ombudsman’s workload. Therefore, this study provides a meaningful contribution to improving the quality of services in maladministration handling by the Aceh Ombudsman Office in the future to cases reported by the citizens.